Insulation breakdown resistant composite filler, preparation method and application

By pretreating basalt scales and mixing them with nanocellulose, the problem of difficulty in bonding the interface between organic fibers and inorganic basalt scales is solved, and the mechanical strength and insulation performance of insulating paper are improved.

CN119711239AActive Publication Date: 2025-03-28SHAANXI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411928967.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The interface between organic fibers and inorganic basalt scales is difficult to combine during the composite process, resulting in poor mechanical properties of the paper and affecting the performance and service life of insulating paper.

Method used

The basalt scales were pretreated and mixed with nanocellulose, grinding and ultrasonic centrifugation were performed to remove unstripped basalt scales to obtain nanocellulose-basalt nanosheet composite filler.

Benefits of technology

It realizes the effective combination of organic fibers and basalt scales, improves the mechanical strength, insulation performance, weather resistance and heat insulation properties of insulating paper, and extends the service life of insulating paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711239A_ABST
    Figure CN119711239A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of insulating material preparation, in particular to an insulation breakdown resistant composite filler, a preparation method and application, and the method comprises the following steps: pretreating basalt flakes to remove impurities in the basalt flakes; according to the preparation method, pretreated basalt scales and nano cellulose are mixed and ground to obtain a mixture, in the process, due to the introduction of a ball milling process and nano fibers, efficient stripping of the basalt scales can be realized, and the basalt scales form finer and more uniform scale particles; the scale particles can be fully interwoven with the nanocellulose to form a tightly combined composite material; and diluting the mixture in water, and removing unstripped basalt scales to obtain the composite filler. The composite filler realizes effective combination of organic fibers and basalt scales, and has excellent mechanical properties and mechanical properties. The problems that interfaces of organic fibers and inorganic basalt scales are difficult to combine, and the mechanical performance of the paper is affected are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulating material preparation, in particular to a composite filler resistant to insulation breakdown, a preparation method and application thereof. Background Art

[0002] Cellulose materials are widely used in electrical insulation due to their low cost and renewability. However, traditional cellulose paper has some inherent defects, such as susceptibility to moisture, high porosity and insufficient heat resistance, which may affect the performance and service life of insulation paper. In order to solve these problems and improve the quality and stability of electronic products, it is particularly important to modify the paper.

[0003] At present, researchers mainly use two approaches, chemical modification and compounding with other materials, to improve the performance and stability of cellulose-based sound-absorbing materials. Among them, composite materials have been widely developed because the performance and structure of each component can be designed and optimized as needed to obtain excellent comprehensive performance. By compounding with other high-performance materials, the interface performance and insulation capacity of cellulose materials can be improved, while the mechanical strength and temperature resistance of insulating materials can be enhanced, improving their performance in complex environments and meeting higher levels of insulation requirements.

[0004] Basalt flakes are a high-performance inorganic material. They are made from natural basalt ores with excellent performance through special processes such as high-temperature melting, clarification, homogenization, and screening. The thickness is generally around 2-6μm, and the area varies, usually around 0.5mm. 2 ~5mm 2 About. Due to the high content of silica and alumina in basalt flakes, basalt flakes not only have insulation properties, but also have unique advantages in acid and alkali resistance and corrosion resistance. Its operating temperature range is -200℃-1100℃, which can adapt to special environments with large temperature differences and particularly harsh conditions. However, since the interface between organic fibers and inorganic basalt flakes is difficult to combine, a large number of defects will be generated during the composite process, which directly affects the mechanical properties of the paper and hinders the development of basalt flakes in the field of insulating paper manufacturing. Summary of the invention

[0005] Aiming at the problem in the prior art that the interface between organic fiber and inorganic basalt flakes is difficult to combine, which affects the mechanical properties of paper, the present invention provides a composite filler resistant to insulation breakdown, a preparation method and an application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a composite filler resistant to insulation breakdown, comprising: Pre-treating the basalt flakes to obtain pre-treated basalt flakes; The pretreated basalt flakes are mixed with nanocellulose and ground to obtain a mixture; the mixture includes nanocellulose-basalt nanosheet composite filler and unpeeled basalt flakes; The mixture was diluted in water and the unexfoliated basalt flakes were removed to obtain a composite filler.

[0007] Optionally, the method for pretreating basalt flakes is: The basalt flakes are dispersed in deionized water, and are stirred, allowed to stand, filtered and dried in sequence to obtain pretreated basalt flakes; wherein the stirring speed is 100-400 r / min, the standing time is 1-2 min, the filtering mesh size is 100-150 meshes, and the drying temperature is 100° C.-120° C.

[0008] Optionally, the mass ratio of the pretreated basalt flakes to the nanocellulose is (1:3) to (3:1), the grinding speed is 250 to 550 r / min, and the grinding time is 0.5 to 4 h.

[0009] Optionally, the method of diluting the mixture in water and removing the unpeeled basalt flakes to obtain the composite filler is: The mixture was diluted in water to obtain a mixed suspension; The mixed suspension is subjected to ultrasonic treatment to obtain a uniformly dispersed mixed suspension; The uniformly dispersed mixed suspension is centrifuged, and the supernatant is retained to obtain a composite filler.

[0010] Optionally, the solid concentration in the mixed suspension is 0.1% to 1%; the power of the ultrasonic treatment is 500 to 1000 W, and the ultrasonic time is 10 to 60 min; the speed of the centrifugal treatment is 500 to 2500 r / min, and the time is 5 to 25 min.

[0011] A composite filler resistant to insulation breakdown is prepared by using the method.

[0012] A method for preparing insulating paper using the above-mentioned composite filler resistant to insulation breakdown comprises: mixing the composite filler with softwood pulp to obtain a mixed pulp; The mixed slurry is sequentially subjected to delamination, sheet making, suction filtration, drying and hot pressing to obtain insulating paper.

[0013] Optionally, in the process of mixing the composite filler with the coniferous wood pulp, the amount of the composite filler added is 5% to 30% by mass.

[0014] Optionally, in the process of sequentially deflaking, sheeting, filtering, drying and hot pressing the mixed slurry to obtain insulating paper, the deflaking rotation number is 6000-10000r, the drying temperature is 80℃-120℃, the drying time is 5-20min, the hot pressing temperature is 100-120℃, and the hot pressing time is 5-20min.

[0015] An insulating paper is prepared by using the composite filler resistant to insulation breakdown.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a method for preparing a composite filler resistant to insulation breakdown. The method comprises the following steps: pretreating basalt flakes to obtain pretreated basalt flakes, so as to remove impurities in the basalt flakes, which is conducive to the basalt flakes forming a good insulation layer in the composite filler; then, the pretreated basalt flakes are mixed with nanocellulose and ground to obtain a mixture. In this process, due to the ball milling process and the introduction of nanofibers, the basalt flakes can be efficiently stripped, so that the basalt flakes form finer and more uniform flake particles, which can be fully interwoven with the nanocellulose to form a tightly combined composite material; since the ground mixture includes a nanocellulose-basalt nanosheet composite filler and unstripped basalt flakes, the mixture is further treated, the mixture is diluted in water, and the unstripped basalt flakes are removed to obtain the composite filler. This composite filler achieves an effective combination of organic fibers and basalt flakes, and has excellent mechanical properties, weather resistance, corrosion resistance, sound absorption and thermal insulation properties. The nanocellulose-basalt nanosheet composite filler reinforced insulating paper prepared using this filler has good mechanical strength and insulation properties, laying the foundation for improving the performance of insulating paper. The preparation method is simple and easy to operate, does not require large-scale equipment, and is relatively easy to achieve industrialization, which increases the possibility of industrial mass production.

[0017] The method for pretreating basalt flakes is to disperse the basalt flakes in deionized water, and sequentially stir, stand, filter and dry to obtain pretreated basalt flakes; wherein the stirring speed is 100-400r / min, the standing time is 1-2min, the filtration mesh is 100-150 mesh, and the drying temperature is 100°C-120°C. This method can make the basalt flakes dispersed evenly in water, make the flakes dispersed more evenly in water, and may promote the activation of the flake surface, improve the efficiency of subsequent treatment, and provide a good foundation for subsequent treatment.

[0018] The mass ratio of the pretreated basalt flakes and nanocellulose is (1:3) to (3:1), the grinding speed is 250 to 550 r / min, and the grinding time is 0.5 to 4 hours. The basalt flakes have high strength and rigidity, while the nanocellulose has excellent flexibility and toughness. Mixing and grinding the two in a certain proportion can fully combine them to form a composite material with excellent mechanical properties.

[0019] The method of diluting the mixture in water and removing the unpeeled basalt flakes to obtain the composite filler is to dilute the mixture in water to obtain a mixed suspension; then, subject the mixed suspension to ultrasonic treatment to obtain a uniformly dispersed mixed suspension; finally, subject the uniformly dispersed mixed suspension to centrifugation treatment, retain the supernatant, and obtain the composite filler. The unpeeled basalt flakes in the mixture can be quickly removed by ultrasonic centrifugation treatment, and the composite of pure nanocellulose and basalt flakes can be retained to obtain a pure and uniform composite filler.

[0020] The present invention also provides a composite filler resistant to insulation breakdown, which is prepared by the above method. The composite filler has excellent insulation breakdown strength, good overall structural stability and durability, and can meet application requirements in different fields.

[0021] The present invention also provides a method for preparing insulating paper using the above-mentioned composite filler resistant to insulation breakdown, wherein the composite filler is mixed with coniferous wood pulp to obtain a mixed slurry; the mixed slurry is sequentially subjected to delamination, sheet making, suction filtration, drying and hot pressing to obtain insulating paper, and the preparation method is simple, easy to operate, does not require modification of the original equipment, is low in cost, and is easy to industrialize. The prepared insulating paper has mechanical properties such as super strong breakdown resistance.

[0022] The present invention provides an insulating paper, which is prepared using the above-mentioned composite filler resistant to insulation breakdown. The insulating paper has excellent insulation performance, high insulation resistance, and can effectively prevent current from passing through, thereby protecting the safety of circuits and equipment. The insulating paper has broad application prospects in the fields of electrical equipment, electronic products, etc., and can be used to manufacture various insulating components and packaging materials. In addition, the insulating paper also has high heat resistance and flame retardancy, good plasticity and processability, and can maintain stable performance in a high temperature environment, which is of great significance for electrical equipment, electronic products, etc. that need to be used in high temperature or flammable environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a schematic flow chart of a method for preparing a composite filler resistant to insulation breakdown.

[0024] Figure 2The Tyndall effect and ultraviolet-near-infrared absorption spectrum of the aqueous dispersion of the composite filler prepared in Example 1 of the present invention.

[0025] Figure 3 This is a transmission electron microscope image of the composite filler prepared in Example 2 of the present invention.

[0026] Figure 4 These are AFM images of the composite filler prepared in Example 3 of the present invention and statistical graphs of the horizontal and vertical dimensions of basalt nanosheets; wherein, a is an atomic force microscope morphology image; b is a statistical graph of the horizontal dimensions of the composite filler, and c is a statistical graph of the thickness dimensions of the composite filler.

[0027] Figure 5 This is an infrared spectrum of the composite filler at different grinding times in Example 4 of the present invention.

[0028] Figure 6 These are breakdown strength images of insulating paper with different proportions of composite fillers prepared in Example 12 of the present invention and the comparative example, as well as field emission scanning electron microscope images of the breakdown points of the insulating paper; wherein, a is a breakdown strength image of insulating paper with different proportions of composite fillers added; b is a scanning electron microscope image of the points where the insulating paper is electrically broken down; and c is a scanning electron microscope image of the breakdown points at a magnified multiple.

[0029] Figure 7 The tensile curves and strength, elongation, toughness and modulus statistical graphs of the insulating paper with different proportions of composite fillers added prepared in Example 12 of the present invention and the comparative example, wherein a is the tensile test stress-strain curve of the insulating paper with different proportions of composite fillers added; b is the toughness and tightness of the insulating paper with different proportions of composite fillers added; c is the tensile strength and Young's modulus of the insulating paper with different proportions of composite fillers added. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0031] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0032] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0033] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0034] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0036] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0037] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0038] The present invention discloses a method for preparing a composite filler resistant to insulation breakdown. Figure 1 ,include: S1: pre-treating the basalt flakes to obtain pre-treated basalt flakes, specifically: The basalt flakes are dispersed in deionized water, and stirred, allowed to stand, filtered and dried in sequence to obtain pretreated basalt flakes; wherein, the stirring speed is 100-400 r / min, preferably 150-300 r / min, and more preferably 180-250 r / min; the standing time is 1-2 min, and more preferably 2 min; the filtration mesh size is 100-150 mesh, and more preferably 120-150 mesh, and more preferably 130-150 mesh; the drying temperature is 80°C-120°C, and more preferably 100°C-110°C, and more preferably 105°C-110°C.

[0039] S2: mixing the pretreated basalt flakes with nanocellulose and grinding them to obtain a mixture; the mixture includes nanocellulose-basalt nanosheet composite filler and unpeeled basalt flakes, specifically: The pretreated basalt flakes and nanocellulose are mixed in a mass ratio of (1:3) to (3:1), preferably (1:2) to (3:1), and more preferably (2:1) to (3:1), and placed in a ball mill, and ground at a speed of 250 to 550 r / min, preferably 300 to 550 r / min, and more preferably 400 to 550 r / min for 0.5 to 4 hours, preferably 2 to 4 hours, and more preferably 3 to 4 hours to obtain a mixture; the nanocellulose includes TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) oxidized nanocellulose, but is not limited to TEMPO oxidized nanocellulose.

[0040] S3: diluting the mixture in water and removing the unpeeled basalt flakes to obtain a composite filler, specifically: Diluting the mixture in water to obtain a mixed suspension; wherein the solid concentration in the mixed suspension is 0.1% to 1%, preferably 0.3% to 0.7%, and more preferably 0.5% to 0.7%; The mixed suspension is subjected to ultrasonic treatment to obtain a uniformly dispersed mixed suspension; wherein the power of the ultrasonic treatment is 500-1000W, preferably 600-800W, more preferably 600-800W, and the ultrasonic time is 10-60min, preferably 15-40min, more preferably 20-40min; The uniformly dispersed mixed suspension is centrifuged, and the supernatant is retained to obtain a composite filler; the rotation speed of the centrifugal treatment is 500-2500r / min, preferably 800-2500r / min, and more preferably 1000-2500r / min, and the time is 5-25min, preferably 8-20min, and more preferably 10-15min.

[0041] The present invention provides a composite filler resistant to insulation breakdown, which is prepared by the above method. The composite filler has excellent insulation breakdown strength, good overall structural stability and durability, and can meet application requirements in different fields.

[0042] The present invention also provides a method for preparing insulating paper using the above-mentioned composite filler resistant to insulation breakdown, comprising: The composite filler is mixed with coniferous wood pulp to obtain a mixed pulp; wherein, in the process of mixing the composite filler with coniferous wood pulp, the amount of the composite filler added is 5% to 30%; The mixed slurry is sequentially deflated, sheeted, filtered, dried and hot pressed to obtain insulating paper; wherein, the deflation speed is 6000-10000r, the drying temperature is 80℃-120℃, the drying time is 5-20min, the hot pressing temperature is 100-120℃, and the hot pressing time is 5-20min.

[0043] The present invention provides an insulating paper, which is prepared using the above-mentioned composite filler resistant to insulation breakdown. The insulating paper has excellent insulation performance, high insulation resistance, and can effectively prevent current from passing through, thereby protecting the safety of circuits and equipment. The insulating paper has broad application prospects in the fields of electrical equipment, electronic products, etc., and can be used to manufacture various insulating components and packaging materials. In addition, the insulating paper also has high heat resistance and flame retardancy, good plasticity and processability, and can maintain stable performance in a high temperature environment, which is of great significance for electrical equipment, electronic products, etc. that need to be used in high temperature or flammable environments.

[0044] Example 1 The basalt flakes (BS) were dispersed in deionized water and stirred at a speed of 200r / min. When the basalt flakes were uniformly dispersed in the water, the stirring was stopped. After standing for 1min, the basalt flake suspension was filtered and dried. The mesh size of the filtration was 100 meshes and the drying temperature was 80℃ to obtain the pretreated basalt flakes. Then the pretreated basalt flakes were mixed with nanocellulose in a ratio of 1:3, ground at a speed of 250r / min for 0.5h, and then the grinding product was collected to obtain a mixture of nanocellulose-basalt nanosheet composite filler and unpeeled basalt flakes. The mixture was diluted in deionized water with a dilution concentration of 0.1%, and then placed in an ultrasonic machine for ultrasonic treatment at a power of 500W for 10min. Finally, the ultrasonically treated mixed solution was placed in a centrifuge tube and centrifuged at a speed of 500r / min for 5min. The supernatant obtained by centrifugation was the aqueous dispersion of the composite filler, which was sealed and stored for use.

[0045] See also Figure 2The composite filler prepared in this embodiment was subjected to Tyndall effect and ultraviolet-near-infrared absorption spectrum tests. The results showed that the composite filler was a uniform and transparent light gray colloid. The band gap width of the composite filler was 5.48 eV, which was judged to be an insulator.

[0046] Example 2 The basalt flakes are dispersed in deionized water and stirred at a speed of 200 r / min. The stirring is stopped when the basalt flakes are evenly dispersed in the water. After standing for 2 minutes, the basalt scale suspension is filtered and dried. The filtration mesh size is 150 mesh and the drying temperature is 90°C to obtain pretreated basalt scales; the pretreated basalt scales are then mixed with nanocellulose in a ratio of 1:2, ground at a speed of 300 r / min for 1 hour, and then the ground products are collected to obtain a mixture of nanocellulose-basalt nanosheet composite filler and unpeeled basalt scales.

[0047] The mixture was diluted in deionized water with a dilution concentration of 0.3%, and then placed in an ultrasonic machine for ultrasonic treatment at a power of 600 W for 20 min. Finally, the ultrasonically treated mixed solution was placed in a centrifuge tube and centrifuged at a speed of 1000 r / min for 10 min. The supernatant obtained by centrifugation was the aqueous dispersion of the composite filler, which was sealed and stored for later use.

[0048] See also Figure 3 The composite filler prepared in the example was tested by transmission electron microscopy, and it was found that the composite filler was composed of basalt nanosheets with a diameter of about 300 nm and nanocellulose with a diameter of less than 10 nm.

[0049] Example 3 The basalt flakes are dispersed in deionized water and stirred at a speed of 200 r / min. The stirring is stopped when the basalt flakes are evenly dispersed in the water. After standing for 1 minute, the basalt scale suspension is filtered and dried. The filtration mesh size is 100 mesh and the drying temperature is 100°C to obtain pretreated basalt scales; the pretreated basalt scales are then mixed with nanocellulose in a ratio of 2:1, ground at a speed of 350 r / min for 2 hours, and then the ground products are collected to obtain a mixture of nanocellulose-basalt nanosheet composite filler and unpeeled basalt scales.

[0050] The mixture was diluted in deionized water with a dilution concentration of 0.5%, and then placed in an ultrasonic machine for ultrasonic treatment at a power of 700 W for 30 minutes. Finally, the ultrasonically treated mixed solution was placed in a centrifuge tube and centrifuged at a speed of 1500 r / min for 15 minutes. The supernatant obtained by centrifugation was the aqueous dispersion of the composite filler, which was sealed and stored for later use.

[0051] See also Figure 4 The prepared composite filler was subjected to atomic force testing. From the AFM images and the horizontal and vertical dimension statistics of the basalt nanosheets, it can be seen that the average thickness of the basalt nanosheets in the composite filler is 1.5nm, and the average diameter is 300nm, while the diameter of nanocellulose is generally greater than 2.5nm, and the length is between 100nm and 500nm.

[0052] Example 4 The basalt flakes are dispersed in deionized water and stirred at a speed of 200 r / min. The stirring is stopped when the basalt flakes are evenly dispersed in the water. After standing for 2 minutes, the basalt scale suspension is filtered and dried. The filtration mesh size is 150 mesh and the drying temperature is 105°C to obtain pretreated basalt scales; then the pretreated basalt scales are mixed with nanocellulose in a ratio of 1:1, and ground at a speed of 400 r / min for 0h, 1h, 2h, 4h and 6h respectively, and then the grinding products are collected respectively to obtain a mixture of nanocellulose-basalt nanosheet composite filler and unpeeled basalt scales.

[0053] The mixture was diluted in deionized water with a dilution concentration of 0.7%, and then placed in an ultrasonic machine for ultrasonic treatment at a power of 800 W for 40 minutes. Finally, the ultrasonically treated mixed solution was placed in a centrifuge tube and centrifuged at a speed of 2000 r / min for 20 minutes. The supernatant obtained by centrifugation was the aqueous dispersion of the composite filler, which was sealed and stored for later use.

[0054] See also Figure 5 From the infrared spectra of the composite fillers after ball milling for different times, it can be seen that with the increase of ball milling time, the hydroxyl peak of the composite filler increases from 3600cm -1 Moved to 3700cm nearby -1 Nearby, the hydroxyl peak red-shifted, indicating that the surface of nanocellulose produced hydrogen bonds with the surface of basalt nanosheets.

[0055] Example 5 The basalt flakes are dispersed in deionized water and stirred at a speed of 200 r / min. The stirring is stopped when the basalt flakes are evenly dispersed in the water. After standing for 1 minute, the basalt scale suspension is filtered and dried. The filtration mesh size is 100 mesh and the drying temperature is 110°C to obtain pretreated basalt scales; the pretreated basalt scales are then mixed with nanocellulose in a ratio of 3:1, ground at a speed of 450 r / min for 4 hours, and then the ground products are collected to obtain a mixture of nanocellulose-basalt nanosheet composite filler and unpeeled basalt scales.

[0056] The mixture was diluted in deionized water with a dilution concentration of 0.9%, and then placed in an ultrasonic machine for ultrasonic treatment at a power of 900 W for 50 min. Finally, the ultrasonically treated mixed solution was placed in a centrifuge tube and centrifuged at a speed of 2500 r / min for 25 min. The supernatant obtained by centrifugation was the aqueous dispersion of the composite filler, which was sealed and stored for later use.

[0057] Example 6 The basalt flakes are dispersed in deionized water and stirred at a speed of 200 r / min. The stirring is stopped when the basalt flakes are evenly dispersed in the water. After standing for 2 minutes, the basalt scale suspension is filtered and dried. The filtration mesh size is 150 mesh and the drying temperature is 120°C to obtain pretreated basalt scales; the pretreated basalt scales are then mixed with nanocellulose in a ratio of 2:3, ground at a speed of 500 r / min for 0.5 h, and then the ground products are collected to obtain a mixture of nanocellulose-basalt nanosheet composite filler and unpeeled basalt scales.

[0058] The mixture was diluted in deionized water with a dilution concentration of 1%, and then placed in an ultrasonic machine for ultrasonic treatment at a power of 1000 W for 60 min. Finally, the ultrasonically treated mixed solution was placed in a centrifuge tube and centrifuged at a speed of 2500 r / min for 25 min. The supernatant obtained by centrifugation was the aqueous dispersion of the composite filler, which was sealed and stored for later use.

[0059] Example 7 The composite filler prepared in Example 2 was added into the coniferous wood pulp at a ratio of 5% for mixing and decomposition at a decomposition speed of 7000 r. The mixed pulp was filtered using a paper sheet making machine, then dried for 10 minutes at a drying temperature of 90°C, and finally hot pressed at 105°C for 10 minutes to obtain a composite paper with high insulation properties.

[0060] Example 8 The composite filler prepared in Example 3 was added into the coniferous wood pulp at a ratio of 10% for mixing and decomposition at a decomposition speed of 8000 r. The mixed pulp was filtered using a paper sheet making machine, then dried for 15 minutes at a drying temperature of 100°C, and finally hot pressed at 110°C for 15 minutes to obtain a composite paper with high insulation properties.

[0061] Example 9 The composite filler prepared in Example 4 was added into the coniferous wood pulp at a ratio of 15% for mixing and decomposition at a decomposition speed of 9000 r. The mixed pulp was filtered using a paper sheet making machine, then dried for 20 minutes at a drying temperature of 105°C, and finally hot pressed at 115°C for 20 minutes to obtain a composite paper with high insulation properties.

[0062] Example 10 The composite filler prepared in Example 5 was added into the coniferous wood pulp at a ratio of 20% for mixing and decomposition at a decomposition speed of 10000 r. The mixed pulp was filtered using a paper sheet making machine, then dried for 10 min at a drying temperature of 110°C, and finally hot pressed at 120°C for 10 min to obtain a composite paper with high insulation properties.

[0063] Embodiment 11 The composite filler prepared in Example 6 was added into the coniferous wood pulp at a ratio of 20% for mixing and decomposition at a decomposition speed of 10000 r. The mixed pulp was filtered using a paper sheet making machine, then dried for 10 min at a drying temperature of 110°C, and finally hot pressed at 120°C for 10 min to obtain a composite paper with high insulation properties.

[0064] Example 12 The composite filler prepared in Example 1 was deflaked with coniferous wood pulp at 2%, 5%, 10%, 20% and 30% respectively at a deflaking speed of 6000r. The mixed pulp was filtered using a paper sheet making machine, then dried for 5 minutes at a drying temperature of 80°C, and finally hot pressed at 100°C for 5 minutes to obtain a composite paper with high insulation properties.

[0065] Comparative Example The coniferous wood pulp was directly deflagrated at a deflagration speed of 6000r, and the mixed pulp was filtered using a paper sheet machine, followed by drying for 5 minutes at a drying temperature of 80°C, and finally hot pressing at 100°C for 5 minutes to obtain a composite paper with high insulation properties.

[0066] The insulation paper prepared in Example 12 and the comparative example was subjected to a breakdown strength test. With the addition of the composite filler, the breakdown strength of the composite paper was significantly improved. When the addition ratio was 15%, the composite paper reached the highest breakdown strength of 72.7 kV / mm. It can be seen from the field emission scanning electron microscope image that the composite filler makes the surface and interior of the paper denser, effectively preventing dendrite breakdown.

[0067] See also Figure 7The mechanical properties of the insulating paper prepared in Example 12 and the comparative example were tested, and it was found that the composite filler has a reinforcing and toughening effect on the insulating paper. When the addition ratio is 10%, the best tensile strength is 102 MPa.

[0068] In summary, the present invention provides a composite filler resistant to insulation breakdown, a preparation method and an application. By introducing nanocellulose and ball milling technology, it is possible to achieve efficient peeling of basalt flakes and form a tightly bonded composite material with nanocellulose. The prepared nanocellulose-basalt nanosheet composite filler reinforced insulating paper has good mechanical strength and insulation properties, and is also an advanced composite material with other excellent environmental tolerance capabilities, meeting the needs of special fields such as aerospace. The preparation method is simple and easy to operate, does not require large-scale equipment, and is relatively easy to achieve industrialization, which increases the possibility of industrial mass production.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A method for preparing a composite filler resistant to insulation breakdown, characterized in that: include: Pre-treating the basalt flakes to obtain pre-treated basalt flakes; The pretreated basalt flakes are mixed with nanocellulose and ground to obtain a mixture; the mixture includes nanocellulose-basalt nanosheet composite filler and unpeeled basalt flakes; The mixture was diluted in water and the unexfoliated basalt flakes were removed to obtain a composite filler.

2. The method for preparing a composite filler resistant to insulation breakdown according to claim 1, characterized in that: The method for pre-treating basalt flakes is as follows: The basalt flakes are dispersed in deionized water, and are stirred, allowed to stand, filtered and dried in sequence to obtain pretreated basalt flakes; wherein the stirring speed is 100-400 r / min, the standing time is 1-2 min, the filtering mesh size is 100-150 meshes, and the drying temperature is 100° C.-120° C.

3. The method for preparing a composite filler resistant to insulation breakdown according to claim 1, characterized in that: The mass ratio of the pretreated basalt flakes to the nanocellulose is (1:3) to (3:1), the grinding speed is 250 to 550 r / min, and the grinding time is 0.5 to 4 hours.

4. The method for preparing a composite filler resistant to insulation breakdown according to claim 1, characterized in that: The method of diluting the mixture in water and removing the unpeeled basalt flakes to obtain the composite filler is: The mixture was diluted in water to obtain a mixed suspension; The mixed suspension is subjected to ultrasonic treatment to obtain a uniformly dispersed mixed suspension; The uniformly dispersed mixed suspension is centrifuged, and the supernatant is retained to obtain a composite filler.

5. The method for preparing a composite filler resistant to insulation breakdown according to claim 4, characterized in that: The solid concentration in the mixed suspension is 0.1% to 1%; the power of the ultrasonic treatment is 500 to 1000 W, and the ultrasonic time is 10 to 60 minutes; the speed of the centrifugal treatment is 500 to 2500 r / min, and the time is 5 to 25 minutes.

6. A composite filler resistant to insulation breakdown, characterized in that: Prepared by the method described in any one of claims 1 to 5.

7. A method for preparing insulating paper using the composite filler resistant to insulation breakdown according to claim 6, characterized in that: include: mixing the composite filler with softwood pulp to obtain a mixed pulp; The mixed slurry is sequentially subjected to delamination, sheet making, suction filtration, drying and hot pressing to obtain insulating paper.

8. The method for preparing insulating paper according to claim 7, characterized in that: In the process of mixing the composite filler with the coniferous wood pulp, the amount of the composite filler added is 5% to 30% by mass.

9. The method for preparing insulating paper according to claim 7, characterized in that: In the process of sequentially deflocculanting, sheeting, filtration, drying and hot pressing the mixed slurry to obtain insulating paper, the deflocculant rotation speed is 6000-10000r, the drying temperature is 80°C-120°C, the drying time is 5-20min, the hot pressing temperature is 100-120°C, and the hot pressing time is 5-20min.

10. An insulating paper, characterized in that: Prepared using the composite filler resistant to insulation breakdown as described in claim 6.

Citation Information

Patent Citations

  • Preparation method of nano-cellulose modified basalt fiber biological filler

    CN115745143A

  • Preparation method of composite filler for papermaking

    CN116289298A

  • Basalt flake / cellulose nanofiber composite aerogel as well as preparation method and application thereof

    CN118307834A

  • Boron nitride / nanocellulose composite high-thermal-conductivity film as well as preparation method and application thereof

    CN118388841A